SHR overexpression induces the formation of supernumerary cell layers with cortex cell identity in rice - Henry, S.; Dievart, A.; Divol, F.; Pauluzzi, G.; Meynard, D.; Swarup, Ranjan; Wu, S.; Gallagher, K.L.; Périn, C. (Elsevier, 2017)
The number of root cortex cell layers varies among plants, and many species have several cortical cell layers. We recently demonstrated that the two rice orthologs of the Arabidopsis SHR gene, OsSHR1 and OsSHR2, could complement the A. thaliana shr mutant. Moreover, OsSHR1 and OsSHR2 expression in A. thaliana roots induced the formation of extra root cortical cell layers. In this article, we demonstrate that the overexpression of AtSHR and OsSHR2 in rice roots leads to plants with wide and short roots that contain a high number of extra cortical cell layers. We hypothesize that SHR genes share a conserved function in the control of cortical cell layer division and the number of ground tissue cell layers in land plants.